The Relation Between Blood Lead Levels and Osteoporosis in Turkish Women - Nurver Turfaner Ertürk; Suphi Vehid; Derviş Özçelik; Metin Hallaç; Sinan Aran; Selmin Toplan; Fikret Sipahioğlu (Galenos Yayinevi, 2004)
Lead is a toxic heavy element which is to 90% deposited in bone until the 6th decade and is given to the blood with pregnancy, lactation and physiologic osteoporosis. When it is over certain amounts it may cause osteoporosis and an increase in cardiac events and cancer. In order to evaluate the effect of menopause and osteoporosis on blood lead 20 post-menopausal osteoporotic, 19 non-osteoporotic and 21 pre-menopausal women were selected and their blood levels were measured. In post-menopausal women, its relation with bone mineral density was also investigated. There was no difference between osteoporotic and non-osteoporotic women and pre and postmenopausal women in terms of blood lead (Pb). There was no relation between age and Pb levels but in non-osteoporotic postmenopausal women there was a negative correlation between Pb levels and duration of menopause. There was no relation between bone mineral density and blood lead whereas blood lead and environmental pollution displayed a meaningful correlation.